Changes in cerebral blood flow during anaesthesia and surgery in the sitting position. Issue 8 (August 1987) - Nelson, R J; Lovick, A H; Pickard, J D; Brice, J; Saunders, D; Horsey, P J
Abstract : Serial measurements of global cerebral blood flow (CBF) were made in 15 patients undergoing elective neurosurgical procedures in the sitting position, using a modified intravenous 133Xenon technique. The mean supine CBF rose from 43 (+/-3) ml/100g/min to 62 (+/-6) ml/100g/min in the sitting position and remained elevated at the end of surgery at 62 (+/-5) ml/100g/min. Both increases in CBF were statistically significant with respect to baseline supine values.